Optical Fiber-Based Monitoring of X-ray Pulse Series from a Linear Accelerator - Jeoffray Vidalot; Adriana Morana; Hicham El Hamzaoui; Aziz Boukenter; Geraud Bouwmans; Andy Cassez; Bruno Capoen; Youcef Ouerdane; Marc Gaillardin; Mohamed Bouazaoui; Sylvain Girard; Philippe Paillet (Radiation, 2021)
We investigated in this work the radioluminescence properties of a Ce-doped multimode silica-based optical fiber (core diameter of 50 µm) manufactured by the sol–gel technique when exposed to the high-energy X-rays (~600 keV) of the ORIATRON facility of CEA. We demonstrated its potential to monitor in real-time the beam characteristics of this facility that can either operate in a pulsed regime (pulse duration of 4.8 µs, maximum repetition rate of 250 Hz) or in a quasi-continuous mode. The radiation-induced emission (radioluminescence and a minor Cerenkov contribution) linearly grew with the dose rate in the 15–130 mGy(SiO2)/s range, and the afterglow measured after each pulse was sufficiently limited to allow a clear measurement of pulse trains. A sensor with ~11 cm of sensitive Ce-doped fiber spliced to rad-hard fluorine-doped optical fiber, for the emitted light transport to the photomultiplier tube, exhibited interesting beam monitoring performance, even if the Cerenkov emission in the transport fiber was also considered (~5% of the signal). The beam monitoring potential of this class of optical fiber was demonstrated for such facilities and the possibilities of extending the dose rate range are discussed based on possible architecture choices such as fiber type, length or size.